Virus-Specific Ribonucleic Acid in the Nucleus and Cytoplasm of Rat Embryo Cells Transformed by Adenovirus Type 2 - Shimada, Koichiro (1972)
Nuclei were isolated from rat embryo cells transformed by adenovirus type 2. Nuclear and cytoplasmic virus-specific ribonucleic acids (RNA) were characterized and quantitated by deoxyribonucleic acid (DNA)-RNA hybrid formation with adenovirus DNA. The results indicate that most, if not all, virus-specific RNA molecules are synthesized in the cell nucleus and subsequently transported into cytoplasm where they degrade with a half-life of 1 to 2 hr. No difference in base sequences between nuclear and cytoplasmic virus-specific RNA species can be detected by hybridization competition experiment with viral DNA.